Editorial: Novel Therapeutic Approaches in Inflammatory Bowel Diseases - Giovanni Pallio (Biomedicines, 2023)
Inflammatory bowel diseases (IBDs) encompass ulcerative colitis (UC) and Crohn’s disease (CD), both of which are inflammatory ailments affecting the gastrointestinal tract [...]